Correlation Study Between Abnormal Morphology of Meibomian Glands and Meibum in Patients With Dry Eye Disease Under in vivo Confocal Microscopy - Zheng, Qian; Xue, Yuanyuan; Zhong, Xiaowei; Li, Guangwei; Shi, Weiyun; Wang, Ting (Frontiers in Medicine, 2022)
Objective: To observe the differences of meibomian gland morphology between meibomian gland dysfunction (MGD) patients with liquid meibum, with solid meibum and non-MGD group using laser scanning in vivo confocal microscopy (IVCM) and then to analyze the correlation between meibomian gland abnormalities and dry eye disease. Methods: 21 MGD patients (42 eyes) with liquid meibum, 21 MGD patients (38 eyes) with solid meibum, and 24 non-MGD patients (39 eyes) were enrolled in the study. The IVCM examination and Schirmer II test were performed and the non-invasive tear-film break-up time (NIBUT) was measured. Results: The data obtained from all the patients were normally distributed, therefore, one-way analysis of variance was used. The meibomian gland opening diameter and the gland opening area of the MGD patients were greater than those of the non-MGD patients, and the values of the liquid meibum group were greater than those of the solid meibum group (F=17.96, p<0.001; F=8.84, p<0.001, respectively). Due to the changes in meibomian gland opening diameter and the dilation of meibomian gland acini, the acinar longest diameter and the unit area of the MGD patients were also greater than those of the non-MGD patients, and the values of the solid meibum group were greater than those of the liquid meibum group (F=36.52, p<0.001; F=27.81, p<0.001, respectively). In the aspect of acinar shortest diameter, there was no difference among the three groups (F=0.24, P>0.05). The highest inflammatory cell density was observed in the solid meibum group, followed by the liquid meibum group and the non-MGD group (F=111.54, p<0.001). Similarly, the results of the Schirmer II test and NIBUT showed that the condition of the MGD patients in the solid meibum group was the worst, followed by the liquid meibum group and the non-MGD group (F=99.57, p<0.001; F=11.87, p<0.001, respectively). Conclusions: Different meibum in MGD patients is accompanied by different meibomian gland morphologies. Compared with patients with liquid meibum, patients with solid meibum have more obvious dilatation of the meibomian glands under confocal microscopy and in these patients, the density of inflammatory cells between glands is higher and the quality of the tears is worse.